Replacing Fat with Soy Milk and Lecithin: Impact on the Quality of Steamed Sponge Cake - Larasita Aulia Putri; Lukman Hidayat; Ulfah Anis; Md Zahidul Islam; Mohammad Qais Rezvani; Kugbere Emumejaye (Journal of Innovation in Applied Natural Science, 2025)
Background of study: Steamed sponge cake is a type of cake that uses eggs as the primary raw material for foam formation, emulsification, and coagulation. Soybean flour, a plant-based protein source, has the potential to replace the functional roles of eggs in steamed sponge preparation. The addition of an emulsifier is also required to maintain the final product quality.Aims and scope of paper: This study aimed to analyze the effects of soy milk substitution, lecithin addition, and their interaction on the physical, chemical, and organoleptic characteristics of steamed sponge cake.Methods: The experiment was conducted using a factorial Completely Randomized Design with two factors: the egg-to-soy milk ratio (100:0, 75:25, and 50:50) and the level of soy lecithin addition (2% and 4%). Data were analyzed using two-way ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) to determine significant differences among treatments.Result: Soy milk significantly affected moisture content, volume, hardness, cohesiveness, springiness, chewiness, gumminess, resilience, protein content, and fat content. Lecithin addition significantly affected moisture content, volume, specific volume, hardness, springiness, chewiness, gumminess, resilience, and protein content. The interaction between soy milk substitution and lecithin addition significantly influenced specific volume, hardness, springiness, gumminess, and resilience.Conclusion: Soy milk substitution and lecithin addition, individually and in combination, significantly influenced multiple physical and chemical properties of steamed sponge cake. These findings demonstrate the potential for partial replacement of eggs with soy milk, combined with soy lecithin, to produce high-quality steamed sponge cake with possible cost benefits.